Solar powered infotainment spot: design, feasibility study and fabrication of an autonomous PV system. Issue 1771 (2015) - Weeda, V.; Isabella, O.; Zeman, M.
ABSTRACT: For increasing the awareness of photovoltaic (PV) conversion and its consumer developments, a PV-powered infotainment spot (information + entertainment) has been recently designed to be used in the campus of Delft University of Technology. This demonstrator provides information to people on campus via a rugged touchscreen that is powered only by solar energy. In this PV system, a 90-W rated flexible CIGS module was deployed as market alternative to rigid c-Si modules. A methodology to accurately estimate the irradiance on a curved plane was developed. Taking into account temperature, irradiance and shading effects, the energy production of the PV module was estimated to be 62 kWh/year. On the other hand, the load should exhibit an energy consumption of 19.3 kWh/year. By means of a 12-V DC mini grid, the excess energy was thus stored in a 120 Ah battery regulated via charge controller or made directly available with two ad-hoc USB ports for smartphone battery recharging. The realized prototype of the infotainment spot is potentially a completely autonomous small-scale PV system with zero loss of load probability.